The Influence of Religiosity, Disclosure of Waqf Fund Management Information and Individual Motivation on Islamic Banking Waqf Fund Participation - Intan, Dewi; Nurhayati, Nunung; Purnamasari, Pupung (Insight Management and Business (IMB), 2024)
This research aims to examine the influence of religiosity, disclosure of waqf fund management information, and individual motivation on participation in Islamic bank waqf funds, focusing on customers of Indonesian Islamic Banks in Bandung City. Using secondary data and a probability sampling technique, specifically stratified random sampling, Cochran's formula determined a sample size of 220 respondents. Data analysis involved descriptive techniques using a Likert scale of 1-5 and verification techniques using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The outer model was evaluated for validity and reliability, while the inner model was assessed by the percentage of variance, with hypothesis testing conducted via Bootstrapping using SmartPLS. Findings indicate that religiosity and individual motivation both have significant positive effects on participation in waqf funds, while disclosure of waqf fund management information does not significantly affect participation. This study contributes original insights by revealing the distinct impacts of these factors on waqf fund participation, providing new knowledge in this area.